Green Building Implementation Challenge for Housing from Developer Perspective in Indonesia - Aisyah Zakiah (Arsitektura : Jurnal Ilmiah Arsitektur dan Lingkungan Binaan, 2023)
The purpose of this study is to examine the challenges of implementing green building concepts for residential buildings from the developer's point of view. Nowadays, housing provision in Indonesia highly depends on the property developer. Hence, the role of property developers in implementing green building concepts in residential buildings is incredibly significant. Data collection was conducted by sending questionnaires to various developers in Indonesia. The result shows that the main challenges in executing the green building concept are the lack of forceful regulations followed by a lack of market technology and training. In addition, during the implementation process, it was discovered that all developers had applied certain green building strategies, such as green area provision, site selection close to public facilities, natural lighting design, and ventilation design.